The Role of Natio-Ethno-Cultural Difference in Narratives of Neighbourhood Change – An Arrival Area in the East German Context - Karin Wiest; Laura Torreiter; Elisabeth Kirndörfer (Tijdschrift voor economische en sociale geografie, 2021)
The article investigates the representations and perceptions of an arrival neighbourhood in the broader context of an urban society with a post-socialist migration history. The study is situated in the East German city of Leipzig, which is characterised by a particular dynamic demographic development and a newly emerging plurality through immigration. By juxtaposing public media coverage about the neighbourhood and subjective perspectives of migrant homeowners and entrepreneurs, the paper approaches societal inclusions and exclusions that take effect through attributions of `natio-ethno-cultural difference'. The media and individual-subjective narratives around the neighbourhood referring to the differentiated logics in dealing with migration reflect power hierarchies on different scales and are linked with the national East-West relation.
Keywords: 330; diversity; media discourse; migrant entrepreneur; neighbourhood change; newspaper analysis